2022
DOI: 10.3389/fcimb.2022.907813
|View full text |Cite
|
Sign up to set email alerts
|

Chimonanthus nitens Oliv. Leaf Granule Ameliorates DSS-Induced Acute Colitis Through Treg Cell Improvement, Oxidative Stress Reduction, and Gut Microflora Modulation

Abstract: The rising incidence of ulcerative colitis has become a new challenge for public health. Chimonanthus nitens Oliv. leaf granule (COG) is a natural medicine used for the treatment of respiratory diseases, which has excellent anti-inflammatory and antioxidant effects. However, the therapeutic effect of COG in ulcerative colitis (UC) has not been reported. Here, the experimental colitis was treated with dextran sodium sulfate (DSS) and COG. After treatment with high (30 g/kg), medium (15 g/kg), and low (7.5 g/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Akkermansia muciniphila was shown to be a human intestinal mucindegrading bacterium (Derrien et al 2004) that can use host-secreted mucus glycoproteins as source of nutrition, leading to erosion of the colonic mucus barrier. Although the intestinal barrier-protective and inflammation-reducing effects of Akkermansia have been reported in many studies, the results of Wang K et al showed an increase in Akkermansia in pathological states, which is consistent with our results (Wang et al 2022;Huang et al 2022). Meanwhile, the controversy over the anti-inflammatory or anti-inflammatory role of Akkermansia was reviewed in a study (Zhang et al 2021b).…”
Section: Discussionsupporting
confidence: 91%
“…Akkermansia muciniphila was shown to be a human intestinal mucindegrading bacterium (Derrien et al 2004) that can use host-secreted mucus glycoproteins as source of nutrition, leading to erosion of the colonic mucus barrier. Although the intestinal barrier-protective and inflammation-reducing effects of Akkermansia have been reported in many studies, the results of Wang K et al showed an increase in Akkermansia in pathological states, which is consistent with our results (Wang et al 2022;Huang et al 2022). Meanwhile, the controversy over the anti-inflammatory or anti-inflammatory role of Akkermansia was reviewed in a study (Zhang et al 2021b).…”
Section: Discussionsupporting
confidence: 91%
“…Alistipes are anaerobic bacteria that are typically found in the healthy human gastrointestinal tract . This study found that the administration of DSS reduced the relative abundance of Alistipes , while both SA and FMT treatments restored this reduction.…”
Section: Discussionmentioning
confidence: 56%
“…Alistipes are anaerobic bacteria that are typically found in the healthy human gastrointestinal tract. 49 This study found that the administration of DSS reduced the relative abundance of Alistipes, while both SA and FMT treatments restored this reduction. Additionally, LPS is known to induce the secretion of various inflammatory cytokines, such as TNF-α, IL-1β, and IL-6, which can lead to an inflammatory immune response.…”
Section: ■ Discussionmentioning
confidence: 59%
“…Basophils increase in Crohn’s disease and UC and favor the mTh17/mTh1 response in MLNs [ 12 ]. There was a significant increase in the frequencies of CD4 + CCR7 − Foxp3 + and CD4 + CCR7 − IL-10 + mTreg cells and a significant decrease in CD4 + CCR7 − IL-17A + mTh17 cells in the MLNs of the mice with DSS-induced experimental colitis [ 36 ]. In the present study, we also found that the colitis mice presented similar results with lower frequencies of mTreg (CD4 + Foxp3 + , CD4 + CCR7 + Foxp3 + , CD4 + CCR7 − Foxp3 + ) cells and higher mTh17 (CD4 + CCR6 + , CD4 + CCR7 + CCR6 + , CD4 + CCR7 − CCR6 + ) cells.…”
Section: Discussionmentioning
confidence: 99%